Shallow tunnel construction technology using pneumatic formwork - Shpakova, H.; Prokopenko, D. (Ways to Improve Construction Efficiency, 2024)
This article considers the technology of underground tunnel construction using pneumatic formwork, which aims to improve and make easier construction of tunnel facilities. Having familiarized with problems of the construction, in particular subway facilities, and analyzed its basic aspects of this construction, I would like to propose using this technology for construction of shallow subway tunnels. The peculiarity of this technology is to optimize a building process and improve quality characteristics of constructed tunnels by replacing prefabricated elements with a solid monolithic tunnel which is built directly on the construction site. The fundamental technological difference is applying pneumatic formwork instead of standard formwork panels and systems of support posts and longitudinal beams. The main working element in pneumatic formwork system is a dome-shaped shell made of a durable membrane that serves as a formwork for concrete. This membrane is filled with air under high pressure using compressors and maintains its shape throughout the entire technological process until the concrete mixture sets. Such pneumatic formwork includes much fewer mounting elements, which improves technical and economic performance. Utilization of pneumatic formwork in modern construction can be a key point in improving technical and economic indices, as construction of such a formwork system takes much less time than for more common panel systems. The development of pneumatic formwork technology has potential not only in the construction of subway but also in other construction areas. As an example, this method can be useful in solving an urgent issue of building bomb shelters for population, and even for enterprises because pneumatic formwork can be made in various shapes depending on the requirements for a particular facility